Hubungan Hukum Tenaga Pendidik dengan Pemilik Lembaga Pendidikan Non Formal Pondok Pesantren Darul Falah Jekulo Kudus - Mumaddun Khaerudin Salami; Hengki Firmanda (Fakultas Hukum Universitas Riau, 2023)
This study aims to determine the legal status that arises as a result of the legal relationship that occurs between the owner of a non-formal educational institution, namely the Darul Falah Jekulo Kudus Islamic boarding school and educators/Ustadz, so that the rights and obligations of the parties in the legal relationship can be known. This research is an empirical normative research. Normative research is conducted by means of library research, to obtain secondary data through document studies. Empirical research is conducted by means of field research, to obtain primary data through the interview method to the respondents. The data analysis used is qualitative, then the results of this research are presented descriptively. The results show that the legal relationship that occurs between the owner of Darul Falah Jekulo Kudus Islamic Boarding School and educators/Ustadz is not included in the employment relationship because it does not fulfill the elements that must exist in the employment agreement.